The development of cash crop economy in Akwanga division, 1908-1960 - Dogara, Ja’afaru Yusuf; Hamidin Abd Hamid (Penerbit Universiti Kebangsaan Malaysia, 2020)
Akwanga division has been a major theater of export crop production and expropriation of other economic resources by the colonial regime, but the Economic History of the area has suffered neglect by scholars in the discipline. This work seeks to examine the evolution of cash crop economy in Akwanga division, north-central Nigeria and the changes brought about by the development. The development of groundnut as a main cash crop in central Nigeria‘s Akwanga division shall also be explore. The study also analyses establishment of produce marketing boards and their roles as catalyst for the distribution of export produce. The work argues that the development of cash crop economy has coopted the people of Central Nigeria into international economy as primary producers of cash crops. The system did not in any way mechanized the agriculture sector and deliberately eschewed possible avenues for the development of individual cultivators. The Historical research method is used to achieve the objectives of this research; primary and secondary data are consulted for the successful completion of the work. This research argues that the increase in demand of groundnut by European manufacturing industries for the production of soap, cooking oil, and margarine has facilitated its production Akwanga division. The work concludes that compulsory labour, taxes, and British currency were introduced as a strategy conceived by the colonial government to implement cash crop production in the study area. Above all the colonial economy did not mechanized agricultural sector and manufacturing industries were not established in Akwanga division. The development of cash crop Economy has incorporated the people of the area into international market as producers of raw materials needed by the European manufacturing companies.